Liquidity factors and liquidity risk management for financial performance improvement in the UAE Islamic banking system - Alqemzi, Abdulla Ateeq Mohammed; Abdul Aziz, Nor Azah; Yahaya, Siti Norbaya; Husseini, Saleh Ali (ASR Research India, 2022)
The purpose of this study is liquidity factors and liquidity risk management to improve financial performance in the Islamic banking system in the United Arab Emirates. The study provides insights for policy makers and practitioners to select appropriate liquidity factor measures for Islamic banks in the UAE, which could eventually enable them to support their own liquidity factor policies, in a way that would expand their client base according to the aspects of liquidity factors, and not just the religious ones. It is also the first study that examines the determinants of liquidity factors in the United Arab Emirates. The study concluded that liquidity factors have a positive and important impact on financial performance. Therefore, it is recommended that banks in the UAE establish sound systems of governance and risk management by developing strategies and policies for liquidity factors that are well integrated into risk management practices as well as putting in place a contingency financing plan to address any liquidity shortfalls during periods of stress or emergency while ensuring that active liquidity control financing needs to avoid any liquidity risk management challenge that may lead to a crisis in banks, is addressed immediately.